Development of biocomposites from poly (lactic acid) and oil palm empty fruit bunch fiber - Rayung, Marwah (2014)
The primary objective of this research was to develop fully biodegradable composite material based on poly(lactic acid) (PLA) and oil palm empty fruit bunch (OPEFB) fiber. However, the incompatibility between PLA and OPEFB fibers lead to poor fiber-matrix adhesion resulted in subpar composites performance. In addition, a typical hybridization of natural fiber/polymer matrix produced dark brown colour of product, a factor that limits its applications. Therefore, efforts had been made to treat the fibers by means of alkaline bleaching by using hydrogen peroxide to remove lignin, hemicellulose and surface impurities. The removal of these components is important to enhance the fiber/matrix interlocking system simultaneously increase the brightness of the composites. From the experimental studies, the optimum condition for bleaching process was obtained at pH 11, 70 °C for 90 minutes. Basically, the bleaching process produced brighter colour fiber with rougher surface as can be observed from Scanning Electron Microscopy (SEM). The Infrared (IR) spectra confirmed the removal of lignin and hemicellulose, while X-Ray Diffraction (XRD) result showed a change in fiber crystallinity from 36.8% to 60.6% after bleaching process due to the removal of these amorphous components. The biocomposites were prepared by mixing PLA with the treated and untreated fiber at different ratio by using internal mixer at temperature 160 °C and 50 rpm. A bright colour biocomposites was successfully produced by using bleached fiber and the addition of colorant improved the appearance. The mechanical properties for bleached fiber biocomposites showed an improvement indicating better fiber-matrix adhesion which is proved by SEM micrographs. Thermal analysis study showed the composites have lower thermal stability compare to neat PLA itself. Water absorption study demonstrated the bleached fiber biocomposite was more water resistance compare to the untreated fiber. At 50% fiber loading, water uptake for bleached fiber biocomposites was recorded at 14.3% whereas 18.7% for untreated fiber biocomposites. Biodegradable study revealed with the addition of fiber into PLA increased the biodegradation rate of the biocomposites. As a matter of fact, the degradation increased because the fiber is more susceptible to microbial attacked, therefore the addition of fiber helps to accelerate the degradation of biocomposites. Besides, treatment of fiber increased the degradation from 6% to 9% after three months burial time. Conclusively, these results supported the role of PLA/OPEFB as environmental friendly composite and showed a great potential as an alternative to the non-biodegradable plastic.